2004
DOI: 10.1080/10412905.2004.9698703
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition of the Essential Oil ofPistacia lentiscusL.

Abstract: The chemical composition of the essential oils, obtained by separate distillation of the leaves, branches and fruits of Pistacia lentiscus from Tuscany (Italy), was analyzed and identified by GC and GC/MS. The leaf oil contained α-pinene (16.1-25.3%), limonene (6.6-12.3%), terpinen-4-ol (7.6-12.7%) and germacrene D (9.6-14.3%) as major components. The branch oil contained α-pinene (34.4-46.2%), myrcene (6.3-11.6%) and limonene (8.1-13.0%), while the fruit oil contained α-pinene (7.5-11.2%), myrcene (68.2-71.0%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…All four species contain α-pinene, ranging from 3.8 % to 15.6 %, while terpinolene is found in concentrations ranging from 0.1 % to 6.9 %. It should be noted that Pistacia terebinthus is characterized by an elevated concentration of limonene (34.2 %) [22], Pistacia atlantica is characterized by an elevated concentration of bornyl acetate (21.5 %) [23], Pistacia lentiscus contained as major components myrcene (68.2-71.0 %) and limonene (9.6-19.7 %) [24] and Pistacia palaestina is characterized by an elevated concentration of (E)-ocimene (41.3 %) and sabinene (20.3 %) [25]. All the major components of the related species are found in P. vera in concentrations amounting to less than 2.5 %.…”
Section: Resultsmentioning
confidence: 99%
“…All four species contain α-pinene, ranging from 3.8 % to 15.6 %, while terpinolene is found in concentrations ranging from 0.1 % to 6.9 %. It should be noted that Pistacia terebinthus is characterized by an elevated concentration of limonene (34.2 %) [22], Pistacia atlantica is characterized by an elevated concentration of bornyl acetate (21.5 %) [23], Pistacia lentiscus contained as major components myrcene (68.2-71.0 %) and limonene (9.6-19.7 %) [24] and Pistacia palaestina is characterized by an elevated concentration of (E)-ocimene (41.3 %) and sabinene (20.3 %) [25]. All the major components of the related species are found in P. vera in concentrations amounting to less than 2.5 %.…”
Section: Resultsmentioning
confidence: 99%
“…The essential oil compositions of hydrodistilled oils from Tuscany and Corsica 27,28 were very similar in the major compounds but several sesquiterpene alcohols, such as cubebol, α-elemol, germacrene-D-4-ol, α-cadinol and α-bisabolol, contained in prevalence in the HD products, have not been reported in P. lentiscus oils from a different geographical origin. In particular, some publications reported α-pinene and terpinen-4-ol as the main components in plants from Morocco and Tunisia.…”
Section: Hd Oil Profilementioning
confidence: 96%
“…lentiscus L. commonly called "Dharw" in Maghreb and "Mustaka" in the Middle East is employed in folk medicine against various pains. The aerial part of this plant has traditionally been used in some regions of Spain as a popular cure against hypertension (Villar et al 1987), and its stimulant and diuretic properties were reported by Vidrich et al (2004).…”
Section: Introductionmentioning
confidence: 99%